Associations Between Canada's Cannabis Legalization and Emergency Department Presentations for Transient Cannabis-Induced Psychosis and Schizophrenia Conditions: Ontario and Alberta, 2015–2019. (August 2022) - Callaghan, Russell C.; Sanches, Marcos; Murray, Robin M.; Konefal, Sarah; Maloney-Hall, Bridget; Kish, Stephen J.
Objective: Cannabis legalization in many jurisdictions worldwide has raised concerns that such legislation might increase the burden of transient and persistent psychotic illnesses in society. Our study aimed to address this issue. Methods: Drawing upon emergency department (ED) presentations aggregated across Alberta and Ontario, Canada records (April 1, 2015–December 31, 2019), we employed Seasonal Autoregressive Integrated Moving Average (SARIMA) models to assess associations between Canada's cannabis legalization (via the Cannabis Act implemented on October 17, 2018) and weekly ED presentation counts of the following ICD-10-CA-defined target series of cannabis-induced psychosis (F12.5; n  = 5832) and schizophrenia and related conditions ("schizophrenia"; F20-F29; n  = 211, 661), as well as two comparison series of amphetamine-induced psychosis (F15.5; n  = 10, 829) and alcohol-induced psychosis (F10.5; n  = 1, 884). Results: ED presentations for cannabis-induced psychosis doubled between April 2015 and December 2019. However, across all four SARIMA models, there was no evidence of significant step-function effects associated with cannabis legalization on post-legalization weekly ED counts of: (1) cannabis-induced psychosis [0.34 (95% CI −4.1; 4.8; P  = 0.88)]; (2) schizophrenia [24.34 (95% CI −18.3; 67.0; P  = 0.26)]; (3) alcohol-induced psychosis [0.61 (95% CI −0.6; 1.8; P  = 0.31); or (4) amphetamine-induced psychosis [1.93 (95% CI −2.8; 6.7; P  = 0.43)]. Conclusion: Implementation of Canada's cannabis legalization framework was not associated with evidence of significant changes in cannabis-induced psychosis or schizophrenia ED presentations. Given the potentially idiosyncratic rollout of Canada's cannabis legalization, further research will be required to establish whether study results generalize to other settings.